1999
DOI: 10.1093/jn/129.9.1705
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Taurine Enhances Cholesterol Degradation and Reduces Serum and Liver Cholesterol Concentrations in Rats Fed a High-Cholesterol Diet

Abstract: The effect of taurine on hypercholesterolemia induced by feeding a high-cholesterol (HC) diet (10g/kg) to rats was examined. When various amounts of taurine (0.25, 0.5, 1, 2.5, 5, 10, 20, 30, 40 or 50 g/kg diet) were supplemented to HC for 2 wk, serum total cholesterol gradually and significantly decreased in a dose-dependent manner and normalized at the dose of 10 g taurine/kg, compared with the control (cholesterol free) diet group. By contrast, serum HDL-cholesterol was elevated by taurine supplementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
4
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(124 citation statements)
references
References 41 publications
6
112
4
2
Order By: Relevance
“…The addition of taurine to a cholesterol-enriched diet, but not to cholesterol-free diets, has been reported to reduce serum and liver cholesterol concentrations, particularly those of cholesteryl ester, in rats (21). We have previously reported that addition of taurine to a diet enriched with cholesterol significantly ameliorated dietary cholesterol-dependent increases in serum and hepatic concentrations of cholesteryl ester of in rats (9).…”
Section: Discussionmentioning
confidence: 88%
“…The addition of taurine to a cholesterol-enriched diet, but not to cholesterol-free diets, has been reported to reduce serum and liver cholesterol concentrations, particularly those of cholesteryl ester, in rats (21). We have previously reported that addition of taurine to a diet enriched with cholesterol significantly ameliorated dietary cholesterol-dependent increases in serum and hepatic concentrations of cholesteryl ester of in rats (9).…”
Section: Discussionmentioning
confidence: 88%
“…From studies in rats, it is known that supplementing low fat, casein-based diets with rather high doses of glycine and/or taurine affects bile acid metabolism (29,70,71). Previously, we have reported that exchanging casein with a glycine-and taurine-rich protein source modulated BA metabolism in low fat fed rats (30).…”
Section: Discussionmentioning
confidence: 95%
“…Supplementing taurine (70,71) or glycine (70) at doses of 50 g/kg diet to casein-based atherogenic diets (containing 1wt% cholesterol and 0.25 wt% cholic acid) has previously been shown to increase fecal BA excretion in rats. Furthermore, the rats treated with the taurine-supplemented diet had higher liver glutathione (GSH) content, decreased liver cholesterol concentration, and higher cholesterol-7a hydroxylase (Cyp7a1) mRNA levels and enzyme activity (71). In this study, the SPH diet provided taurine (1.9 g/kg diet), whereas the casein diet was free of taurine.…”
Section: Nutritional Regulation Of Endogenous Ba Metabolism Modulatesmentioning
confidence: 99%
“…또한, 타우린이 콜레 스테롤 및 지질대사에 미치는 영향에 관하여 활발한 연구가 진행되었다. 다양한 실험 동물을 대상으로 타우린은 기초 사 료를 급여한 고양이 (Cantafora et al, 1991)와 기니아피그 (Cantafora et al, 1986)의 경우 간의 중성지방 함량을 증가시켰으 나, 고지방 사료를 급여한 흰쥐 (Yan et al, 1993;Park and Lee, 1998;Yokogoshi et al, 1999;Yany et al, 2002)에서는 혈 청과 간의 총 콜레스테롤 및 중성지방 함량을 감소시켰고, 토끼 (Petty et al, 1990)에서는 지질 변화가 나타나지 않았다. 따라서 고지방 사료에 타우린의 첨가 효과는 실험 동물의 대상과 특성에 따라 지질대사에 미치는 영향이 다르게 나타 날 수 있다 (Militante and Lombardini, 2004 Means within a raw with no common superscripts differ significantly (P<0.05).…”
unclassified